Retrospective Robot-Measured Upper Limb Kinematic Data From Stroke Patients Are Novel Biomarkers - Goffredo, Michela; Pournajaf, Sanaz; Proietti, Stefania; Gison, Annalisa; Posteraro, Federico; Franceschini, Marco (Frontiers in Neurology, 2021)
Background: The efficacy of upper-limb robot-assisted therapy (ulRT) in stroke subjects is well established. The robot-measured kinematic data can assess the biomechanical changes induced by ulRT and the patient's progress over time. However, literature on the analysis of pre-treatment kinematic parameters as predictive biomarkers of upper limb recovery is limited. Objective: The aim of this study was to calculate pre-treatment kinematic parameters from point-to-point reaching movements in different directions and to identify biomarkers of upper-limb motor recovery in subacute stroke subjects after ulRT. Methods: An observational retrospective study was conducted on 66 subacute stroke subjects who underwent ulRT with an end-effector robot. Kinematic parameters were calculated from the robot-measured trajectories during movements in different directions. A Generalized Linear Model was applied considering the post-treatment Upper Limb Motricity Index and the kinematics parameters (from demanding directions of movement) as dependent variables, and the pre-treatment kinematics parameters as independent variables. Results: A subset of kinematic parameters significantly predicted motor impairment after ulRT: the accuracy in adduction and internal rotation movements of the shoulder was the major predictor of post-treatment Upper Limb Motricity Index. The post-treatment kinematics parameters of the most demanding directions of movement significantly depended on the ability to execute elbow flexion-extension and abduction and external rotation movements of the shoulder at baseline. Conclusions: The multidirectional analysis of robot-measured kinematic data predicts motor recovery in subacute stroke survivors and paves the way in identifying subjects who may benefit more from ulRT.